Accessibility and visually impaired users - Fernandes, António Ramires (2006)
Internet accessibility for the visually impaired community is still an open issue. Guidelines have been issued by the W3C consortium to help web designers to improve web site accessibility. However several studies show that a significant percentage of web page creators are still ignoring the proposed guidelines. Several tools are now available, general purpose, or web specific, to help visually impaired readers. But is reading a web page enough? Regular sighted users are able to scan a web page for a particular piece of information at high speeds. Shouldn't visually impaired readers have the same chance? This paper discusses some features already implemented to improve accessibility and presents a user feedback report regarding the AudioBrowser, a talking browser. Based on the user feedback the paper also suggests some avenues for future work in order to make talking browsers and screen readers compatible.